Aminoglycoside-induced deafness during treatment of acute leukaemia. Issue 2 (19th February 2010) - Bitner-Glindzicz, M; Osei-Lah, V; Colvin, I; Sirimanna, T; Lucas, D; Ardle, B Mac; Webb, D; Shankar, A; Kingston, J; Jenkins, L; Rahman, S
Abstract : Three unrelated children from ethnically diverse backgrounds who were treated for acute leukaemia became profoundly and irreversibly deaf during treatment. Aminoglycoside levels were within the therapeutic range. Genetic testing showed all three to have a maternally inherited mutation of mitochondrial DNA, m.1555A>G, known to cause sensitivity to the ototoxic effects of aminoglycosides. One child has received a cochlear implant, and another will be implanted shortly. Children diagnosed with acute leukaemia should be tested for this mutation at diagnosis, and alternative antibiotics chosen for the treatment of sepsis. Consideration should be given to elective testing of other groups of patients likely to receive aminoglycosides.